Promises and Perils of a Psychopathology of Crime: The Troubling Case of Juvenile Psychopathy - Matthew Owen Howard; James Herbert Williams; Michael George Vaughn; Tonya Edmond (Washington University Journal of Law & Policy, 2004)
In Part I, this Essay describes the historical conceptions of psychopathy, and Part II discusses contemporary perspectives. Part III reviews contemporary juvenile psychopathy assessment measures. In Part IV, the Essay analyzes the factors characteristic of psychopathic youth. Part V reports on pertinent etiological theories. Finally, Part VI suggests directions future research in this field should take. Part VII provides concluding remarks on the troubling case of juvenile psychopathy.
Keywords: Psychology; Pathological; Juvenile delinquents; Delinquent behavior; Clinical legal education; Social science research